EARNINGS QUALITY, CORPORATE GROWTH ON CORPORATE PERFORMANCE: EVIDENCE FROM CONSUMPTION GOOD ON INDONESIAN STOCK EXCHANGE - Indrayati; Widi Dwi Ernawati (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
The purpose of this study is to empirically examine the effect of earnings quality and firm growth on corporate performance. Earnings quality is proxied by discretional accruals, earnings persistence, while corporate growth is proxied by asset growth and profit growth and corporate performance is represented by the returns on equity and assets. This research method uses secondary data with a population of companies with a sample of consumer companies that are listed on the Indonesian stock exchange, namely food, beverage, cigarette and pharmaceutical companies as many as 138 companies for the years 2019-2021. Data collection with documentation and data processing with t test, f test, and coefficient of determination test for multiple linear regression utilizing the traditional assumption test. The results of the partial study (t) show that discretionary accruals, earnings persistence, asset growth and profit growth have a significant effect on corporate performance which is proxied by return on equity and return on assets, joint test (f) shows a significant effect and r square shows influence of 61.28%. The findings show that there is a significant effect of discretionary accruals, earnings persistence, assets growth and earnings growth on corporate performance (ROE and ROA).